H-Bond Surrogate-Stabilized Shortest Single-Turn α-Helices: sp(2) Constraints and Residue Preferences for the Highest α-Helicities - Pal, Sunit (ACS Omega, 2020)
[Image: see text] Short α-helical sequences of proteins fail to maintain their native conformation when taken out of their protein context. Several covalent constraints have been designed, including the covalent H-bond surrogate (HBS)—where a peptide backbone i + 4 → i H-bond is replaced by a covalent surrogate—to nucleate α-helix in short sequences (>7 < 15 amino acids). But constraining the shortest sequences (four amino acids) into a single α-helical turn is still a significant challenge. Here, we introduce an HBS model that can be placed in unstructured tetrapeptides without excising any of its residues, and that biases them predominantly into remarkably stable single α-helical turns in varying solvents, pH values, and temperatures. Circular dichroism (CD), Fourier transform infrared (FT-IR) absorption, one-dimensional (1D)-NMR, two-dimensional (2D)-NMR spectral and computational analyses of the HBS-constrained tetrapeptide analogues reveal that (a) the number of sp(2) atoms in the HBS-constrained backbone influences their predominance and rigidity in the α-helical conformation; and (b) residue preferences at the unnatural HBS-constrained positions influence their α-helicities, with Moc[GFA]G-OMe (1a) showing the highest known α-helicity (θ(n→π*MRE) ∼−25.3 × 10(3) deg cm(2) dmol(–1) at 228 nm) for a single α-helical turn. Current findings benefit chemical biological applications desiring predictable access to single α-helical turns in tetrapeptides.